Using a Third Rider, Donning a Helmet, or Applying Deep Learning for Detection - C. Suresh Kumar, G. Vamsee Krishna, K. Madhavi, M. Akshitha Laasya, K. S. N. Vittal (Mathematical Statistician and Engineering Applications, 2021)
As social, economic, and transportation factors vary from place to place, the number of motorcycle accidents has increased with time in every country. One of the popular forms of transportation for persons in the middle class is the motorcycle. The primary piece of safety gear for motorcycle riders is a helmet, however not all drivers use them. Adults ride at excessive speeds and triples because they don’t follow the required safety precautions. The support that an automobile provides to keep the drivers to be safe and are protected to make a motorcycle accident a severe problem for society. Even when a motorcyclist takes every precaution, incidents with injuries still happen.The key purpose forusing a helmet is towards safeguard wearer’s head which consist of brain in tooccurrence ofcoincidence of accident or the occurrence of bike fall. Today, fewer individuals wear helmets, and many disregard traffic laws like those against triple riding. The suggested project assists in upholding proper triple riding regulations and determining whether motorcycle riders are wearing safety harnesses, or helmets, while operating their vehicles.